Green Economy dan Pembangunan Berkelanjutan di Bali: Systematic Literature Review - Putu Riska Wulandari; Kadek Apriada (RJABM (Research Journal of Accounting and Business Management), 2025)
Although the discourse on the green economy has increasingly gained attention, studies that examine its implementation within cultural-based tourism destinations such as Bali remain scarce. This article seeks to address that gap by conducting a Systematic Literature Review (SLR) of national and international  publications to analyze the relationship between the green economy and sustainable development in Bali. The SLR identifies four key dimensions: the conceptualization of the green economy in the Balinese context, barriers and opportunities for its implementation, relevant indicators, and effective policy strategies. The findings highlight persistent challenges such as fragmented governance, limited infrastructure, and socio-economic constraints, while opportunities arise from the development of green tourism, circular economy practices, and SME innovation supported by traditional village governance. This study contributes theoretically by adapting global green economy frameworks into Bali’s socio-cultural context and practically by providing more integrative policy recommendations. The results underscore that sustainable development in Bali requires strategies that are not only technically feasible but also rooted in local values and community participation.